2013
DOI: 10.1371/journal.pone.0068503
|View full text |Cite
|
Sign up to set email alerts
|

Cotton GhMKK1 Induces the Tolerance of Salt and Drought Stress, and Mediates Defence Responses to Pathogen Infection in Transgenic Nicotiana benthamiana

Abstract: Mitogen-activated protein kinase kinases (MAPKK) mediate a variety of stress responses in plants. So far little is known on the functional role of MAPKKs in cotton. In the present study, Gossypium hirsutum MKK1 (GhMKK1) function was investigated. GhMKK1 protein may activate its specific targets in both the nucleus and cytoplasm. Treatments with salt, drought, and H2O2 induced the expression of GhMKK1 and increased the activity of GhMKK1, while overexpression of GhMKK1 in Nicotiana benthamiana enhanced its tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…This suggested that Sp-miR396a-5p might play a positive role in the regulation of abiotic stress and a negative role in P. nicotianae infection. It is not unusual for a gene to have multiple functions, including those that result in opposing results in the regulation of abiotic and biotic responses Lu et al 2013). Previous studies have indicated that members of the miR396 family also play a role in the response to infection by multiple pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that Sp-miR396a-5p might play a positive role in the regulation of abiotic stress and a negative role in P. nicotianae infection. It is not unusual for a gene to have multiple functions, including those that result in opposing results in the regulation of abiotic and biotic responses Lu et al 2013). Previous studies have indicated that members of the miR396 family also play a role in the response to infection by multiple pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…After 7 days inoculated with P. nicotianae, the tobacco leaves were collected for trypan blue staining assays, performed as described by Lu et al (2013).…”
Section: Pathogen Response Assaysmentioning
confidence: 99%
“…As the nodal point of the MAPK cascades, MAPKKs play paramount roles in amplifying, integrating, and channeling information between the extracellular stimuli and intracellular responses (Kong et al 2011a;Lu et al 2013). L. chinense has great capability for environmental adaption.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that plant MAPKKs can be classified into four distinct groups (A, B, C and D) from the homology analysis of the predicted proteins (Lu et al 2013). The phylogenetic analysis showed that LcMKK exhibited a high similarity with members of the group A MAPKKs, such as AtMKK1 and AtMKK2.…”
Section: Isolation and Sequence Characterization Of Lcmkkmentioning
confidence: 99%
See 1 more Smart Citation